Reflections on the opportunities and challenges of applying experience‐based co‐design (EBCD) to phase 1 clinical trials in oncology - Nils Graber; Nina Canova; Denise Bryant‐Lukosius; Glenn Robert; Blanca Navarro‐Rodrigo; Lionel Trueb; George Coukos; Manuela Eicher; Tourane Corbière; Sara Colomer‐Lahiguera (Wiley, 2024)
Abstract Background Experience‐Based Co‐Design (EBCD) is a multi‐stage participatory action research process which was developed originally to increase patient involvement in service improvement initiatives. This viewpoint article serves as a reflection on the researchers' experiences, focusing on the application and feasibility of participatory approaches, particularly co‐design, in the specific context of early‐phase clinical trials. Methods We reflect on the opportunities and challenges of applying EBCD in a new context of early‐phase clinical trials in oncology where experimental treatments are increasingly perceived as a therapeutic option and, in certain instances, their efficacy may lead to accelerated approval facilitating a swifter integration into standard care. Results We propose that the opportunity of applying EBCD in such trials lies in improving the delivery of person‐centered care, care coordination, and support during the transition from experimental to standard care. Three potential challenges when applying EBCD in early‐phase clinical trials are discussed related to: the need for standardization in trial processes; planning EBCD in a context of high uncertainty; and vulnerability of patient populations. Conclusion Integrating EBCD into early‐phase oncology trials presents an opportunity to enhance person‐centered care and can lead to simultaneous improvements in care processes and therapeutic development. Patient or Public Contribution This article has been developed with the collaboration of a patient partner who serves on the advisory board of our ongoing EBCD study in early clinical trials.